Intracellular Citrate/acetyl-CoA flux and endoplasmic reticulum acetylation: Connectivity is the answer - Gonzalo Fernandez-Fuente; Michael J. Rigby; Luigi Puglielli (Elsevier, 2023)
Background: Key cellular metabolites reflecting the immediate activity of metabolic enzymes as well as the functional metabolic state of intracellular organelles can act as powerful signal regulators to ensure the activation of homeostatic responses. The citrate/acetyl-CoA pathway, initially recognized for its role in intermediate metabolism, has emerged as a fundamental branch of this nutrient-sensing homeostatic response. Emerging studies indicate that fluctuations in acetyl-CoA availability within different cellular organelles and compartments provides substrate-level regulation of many biological functions. A fundamental aspect of these regulatory functions involves Nε-lysine acetylation. Scope of review: Here, we will examine the emerging regulatory functions of the citrate/acetyl-CoA pathway and the specific role of the endoplasmic reticulum (ER) acetylation machinery in the maintenance of intracellular crosstalk and homeostasis. These functions will be analyzed in the context of associated human diseases and specific mouse models of dysfunctional ER acetylation and citrate/acetyl-CoA flux. A primary objective of this review is to highlight the complex yet integrated response of compartment- and organelle-specific Nε-lysine acetylation to the intracellular availability and flux of acetyl-CoA, linking this important post-translational modification to cellular metabolism. Major conclusions: The ER acetylation machinery regulates the proteostatic functions of the organelle as well as the metabolic crosstalk between different intracellular organelles and compartments. This crosstalk enables the cell to impart adaptive responses within the ER and the secretory pathway. However, it also enables the ER to impart adaptive responses within different cellular organelles and compartments. Defects in the homeostatic balance of acetyl-CoA flux and ER acetylation reflect different but converging disease states in humans as well as converging phenotypes in relevant mouse models. In conclusion, citrate and acetyl-CoA should not only be seen as metabolic substrates of intermediate metabolism but also as signaling molecules that direct functional adaptation of the cell to both intracellular and extracellular messages. Future discoveries in CoA biology and acetylation are likely to yield novel therapeutic approaches.